2010
DOI: 10.1016/j.ijdevneu.2010.07.225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inorganic selenium administration in methylmercury‐induced neurotoxicity in mouse cerebral cortex

Abstract: Selenium can counteract methylmercury (MeHg) neurotoxicity. However, data about the neuroprotective effects of sodium selenite (Na(2)SeO(3)) on the activity of mitochondrial complexes and creatine kinase (mtCK) are scarce. Therefore, this study investigated the effects of the chronic exposure to Na(2)SeO(3) on brain energy metabolism and oxidative stress parameters in MeHg-poisoned mice. Adult male mice were orally treated with MeHg (40 mg L(-1) in drinking water, ad libitum) during 21 days and simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 64 publications
5
62
0
Order By: Relevance
“…In addition to this SOD-related research, it has been found in a number of studies that decreased GPx activity in the brains was caused by the mice being given MeHg at a concentration of 40 mg/L in drinking water for several weeks (Carvalho et al, 2007;Farina et al, 2003b;Franco et al, 2009;Glaser et al, 2010). Stringari et al (2008) reported that exposing pregnant mice to MeHg at concentrations of 1, 3, and 10 mg/L in drinking water induced a dose-dependent and long-lasting inhibitory effect on the occurrence of cerebral antioxidant enzymes, such as GPx, which is a developmental phenomenon, in their pups.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 98%
“…In addition to this SOD-related research, it has been found in a number of studies that decreased GPx activity in the brains was caused by the mice being given MeHg at a concentration of 40 mg/L in drinking water for several weeks (Carvalho et al, 2007;Farina et al, 2003b;Franco et al, 2009;Glaser et al, 2010). Stringari et al (2008) reported that exposing pregnant mice to MeHg at concentrations of 1, 3, and 10 mg/L in drinking water induced a dose-dependent and long-lasting inhibitory effect on the occurrence of cerebral antioxidant enzymes, such as GPx, which is a developmental phenomenon, in their pups.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 98%
“…Finally, we did not include in our analysis selenium, a metalloid of considerable interest for human health not only for its own nutritional and toxicological properties [77,78], but also for its ability to modify and generally decrease the biological activity of several heavy metals such as cadmium, lead and mercury. However, the relation of these metals with selenium is very complex and still not well elucidated [79,80], and paradoxically in some cases concurrent administration of selenium along with heavy metals may not mitigate the toxicity of the single elements, but even exacerbate it [77,[81][82][83], further hampering the risk assessment of mixed intake of these elements by seafood [84]. Overall, however, we consider it unlikely that lack of consideration of selenium in the present analysis may have substantially biased our results, though additional research is clearly required to adequately elucidate these potential inhibitory or additive interactions.…”
Section: Estimation Of Risk Assessment Scenariomentioning
confidence: 99%
“…The activities of the respiratory chain mitochondrial complexes I-IV and the mitochondrial creatine kinase activity in cortical mitochondrial preparations were significantly reduced in treated animals. Metal deposits were evident in cortical cells (Glaser et al, 2010) Mercury toxicity in experimental animals and humans (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) Supporting publications 2012:EN-297 139…”
Section: Lipidperoxidationmentioning
confidence: 99%